Advances in Biosensors for Continuous Glucose Monitoring Towards Wearables - Johnston, Lucy; Wang, Gonglei; Hu, Kunhui; Qian, Chungen; Liu, Guozhen (Frontiers in Bioengineering and Biotechnology, 2021)
There exists an ever-growing need for the development of continuous glucose monitors (CGMs) to monitor diabetes non-invasively. Although there are multiple biosensing platforms for monitoring glucose on the market today, there is still a continuous need to improve their precision, repeatability, wearability, and accessibility to end-users. Today, different techniques are being researched. We are increasingly exploring biosensing technologies using different bodily fluids such as sweat and tear fluid, etc., that can be calibrated to and therefore used to measure blood glucose concentrations accurately. To improve the wearability of these devices, exploring different fluids as testing mediums is essential and opens the door to various implants and wearables that in turn have the potential to be less inhibiting to the wearer. Recent developments have appeared in the form of contact lenses or mouthguards for instance. Challenges still present themselves in the form of sensitivity, especially at very high or low glucose concentrations, something critical for a person with diabetes to monitor. This review summarises advances in wearable glucose biosensors over the past five years, comparing the different types as well as the fluid they use to detect glucose, including the CGMs currently available on the market. Perspectives on the development of wearables for glucose biosensing are discussed.